2015
DOI: 10.4149/bll_2015_122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of classic LMA, cobraPLA and V-gel rabbit on QTc interval

Abstract: AIM: We aimed to compare the effects of three different supraglottic airway devices, the classic LMA, PLA, and V-gel, on hemodynamics and QTc in rabbits under general anesthesia. METHOD: The rabbits were divided into four groups: Group C (n = 5) control group with no airway device used, Group L (n = 5, classic LMA), Group P (n = 5, CobraPLA) and Group V (n = 5, V-gel-rabbit). Basal values of heart rate (HR), mean arterial pressure (MAP) and ECG for QTc interval were measured and the measurements were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Lidocaine gel, as a common lubricant and surface anesthetic, is often used to lubricate the LMA and thus prevent and reduce the risk of pharyngeal complications after laryngeal mask anesthesia. 20 However, relevant studies do not support our conclusion and instead considered that the existing lubricants, including lidocaine gel, saline, and other medical lubricants, cannot effectively reduce the risk of pharyngeal complications. 21 , 22 In the current study, however, we confirmed that the use of lidocaine gel may significantly reduce the risk of first-attempt LMA insertion failure, which may help to reduce the risk of complications associated with delayed airway setting.…”
Section: Discussionmentioning
confidence: 60%
“…Lidocaine gel, as a common lubricant and surface anesthetic, is often used to lubricate the LMA and thus prevent and reduce the risk of pharyngeal complications after laryngeal mask anesthesia. 20 However, relevant studies do not support our conclusion and instead considered that the existing lubricants, including lidocaine gel, saline, and other medical lubricants, cannot effectively reduce the risk of pharyngeal complications. 21 , 22 In the current study, however, we confirmed that the use of lidocaine gel may significantly reduce the risk of first-attempt LMA insertion failure, which may help to reduce the risk of complications associated with delayed airway setting.…”
Section: Discussionmentioning
confidence: 60%
“…As described in a previous study, all animals had Rabbit V-gel ® inserted and oxygenation was supported with a mechanical ventilation device with respiration count held to 40/minute appropriate for rabbit physiology with a mix of 50 % oxygen and 50 % air for airway reliability (9). Body temperature was measured with a digital thermometer rectally inserted.…”
Section: Methodsmentioning
confidence: 99%